Peningkatan Hasil Belajar IPS Siswa Kelas V SDN 164 Pacora Kabupaten Soppeng Melalui Metode Thingking Aloud Pair Problem Solving (TAPPS) - Hamriani Hamriani; Qalbi Qalbi (Jurnal PGSD Universitas Lamappapoleonro, 2023)
This study aims to improve student learning outcomes through the Thinking Aloud Pair Problem Solving method in class V SDN 164 Pcora Kabupaten Soppeng. . This research is classroom action research which is carried out in two cycles and through several stages, namely, planning, implementing actions, observing and reflecting. Data was collected using observation sheets, tests and documentation. The data collected were analyzed descriptively and quantitatively. The results showed that student learning outcomes in following the teaching and learning process through the application of the Thinking Aloud Pair Problem Solving learning method could improve social studies learning outcomes for grade VII students of SDN 164 Pacora Kabupaten Soppeng, which can be seen from the completeness of student learning outcomes from 64% completed with a score of 64%. an average of 66.8 in the first cycle increased to 88% completed with an average value of 82 in the second cycle